EPIDERMAL GROWTH-FACTOR AND TRANSFORMING GROWTH-FACTOR-ALPHA CHARACTERISTICS OF HUMAN ORAL-CARCINOMA CELL-LINES - Prime, S. S.; Game, S. M.; Matthews, J. B.; Stone, A.; Donnelly, M. J.; Yeudall, W. A.; PATEL, V; Sposto, R.; Silverthorne, A.; Scully, C. (Stockton Press, 1994)
This study examined the expression of epidermal growth factor (EGF) cell-surface receptors, the response to exogenous ligand and the autocrine production of transforming growth factor a (TGF-a) in normal and carcinoma-derived human oral keratinocytes. One of eight malignant cell lines overexpressed EGF receptors, while the remainder expressed receptor numbers similar to normal cells. Exogenous EGF stimulated incorporation of tritiated thymidine in a dose-dependent manner. In keratinocytes expressing normal numbers of EGF receptors, the cellular response to exogenous EGF correlated positively with total EGF receptor number. SCC-derived keratinocytes produced more TGF-a than normal cells. There was no statistical correlation between the autocrine production of TGF-a, EGF cell-surface receptor expression and cellular response to exogenous EGF. While the growth-stimulatory effects of exogenous TGF-cl were inhibited by the addition of a neutralising antibody, the presence of this antibody in conditioned medium failed to produce a similar decrease in growth. The results indicate that overexpression of EGF receptors is not an invariable characteristic of human oral squamous carcinoma-derived cell lines. Further, the contribution of TGF-a to the growth of normal and carcinoma-derived human oral keratinocytes in vitro may be less significant than previously documented.